Understanding The Text Content: Applying Asking – Question Technique in English Text for Mechanical Engineering Students - Norita Prasetya Wardhani; Muhammad Mujtaba Mitra Zuana (Alsuna: Journal of Arabic and English Language, 2020)
Purpose - The study aims to observe the students ' skills in reading text with the instrument asking and writing the summary results read the text. Design/methodology/approach - To explain the process and the result of students’ writing wrote everything they saw in the class in field notes. Natural design and the phenomenon (descriptive qualitative) were also noted in the field note helping to analyze the data easily. The participants of this study were from mechanical engineering students, 53 students. Findings - The result showed many students could answer the question given and write a summary of the text having been read. Originality/value - Although this research is conducted at the university, the teachers, tutors, and parents to familiarize students or children with questions from the beginning six questions using WH-question mark. This is to train you to ask critically later when you become older. Because actually, the basic question with the WH-question mark is, directing students to take philosophical views. Paper type – Research paper